FACTORS AFFECTING STUDENTS’ ANXIETY IN READING COMPREHENSION OF HIGH SCHOOL STUDENTS IN PALEMBANG - Widya Karamina; Annisa Astrid; Rizqy Dwi Amrina (Universitas Islam Ogan Komering Ilir Kayuagung, 2024)
This research aims to determine the level of students' reading anxiety in English, as well as to identify the causes of reading anxiety. The method of this research is quantitative. The subjects of this study were class XI students at high school in Palembang which amounted to 110 students. The researchers adopted the foreign language reading anxiety scale questionnaire, to examine students' reading anxiety levels. Meanwhile, in investigating students' potential reading anxiety factors, the researchers adopted a ready-made questionnaire. The data were analyzed using descriptive statistics. The results of this study showed that: the level of reading anxiety which was most experienced by 62% of students is a moderate level, and for the major factor that causes students' reading anxiety is an unfamiliar topic 57.95% of students, the second factor is fear of making mistakes with 53.64%, the third factor is worry about the effect of reading with 53.33%, the fourth factor is unknown vocabulary with 52.27%, and students have chosen the last factor is foreign culture with 52%